Everolimus combined with gefitinib in patients with metastatic castration‐resistant prostate cancer: Phase 1/2 results and signaling pathway implications. Issue 21 (15th July 2015) - Rathkopf, Dana E.; Larson, Steven M.; Anand, Aseem; Morris, Michael J.; Slovin, Susan F.; Shaffer, David R.; Heller, Glenn; Carver, Brett; Rosen, Neal; Scher, Howard I.
<x xml:space="preserve">Abstract</x> BACKGROUND The effects of mammalian target of rapamycin (mTOR) inhibition are limited by feedback reactivation of receptor tyrosine kinase signaling in phosphatase and tensin homolog–null tumors. Thus, this study tested the combination of mTOR inhibition (everolimus) and epidermal growth factor receptor inhibition (gefitinib) in castration‐resistant prostate cancer (CRPC). METHODS In phase 1, 12 patients (10 with CRPC and 2 with glioblastoma) received daily gefitinib (250 mg) with weekly everolimus (30, 50, or 70 mg). In phase 2, 27 CRPC patients received gefitinib with everolimus (70 mg). RESULTS Phase 1 revealed no pharmacokinetic interactions and no dose‐limiting toxicities. In phase 2, 18 of 27 patients (67%) discontinued treatment before the 12‐week evaluation because of progression as evidenced by prostate‐specific antigen (PSA) levels (n = 6) or imaging (n = 5) or because of a grade 2 or higher toxicity (n = 7). Thirteen of the 37 CRPC patients (35%) exhibited a rapidly rising PSA level after they had begun treatment, and this declined upon discontinuation. Fluorodeoxyglucose positron emission tomography 24 to 72 hours after the initiation of treatment showed a decrease in the standardized uptake value consistent with mTOR inhibition in 27 of the 33 evaluable patients (82%); there was a corresponding rise in PSA in 20 of these 27 patients (74%). CONCLUSIONS The combination of gefitinib and everolimus did not result in significant antitumor activity. The induction of PSA in tumors treated with mTOR inhibitors was consistent with preclinical data showing that phosphoinositide 3‐kinase (PI3K) pathway signaling feedback inhibits the androgen receptor (AR). This clinical evidence of relief of feedback inhibition promoting enhanced AR activity supports future studies combining PI3K pathway inhibitors and second‐generation AR inhibitors in CRPC. Cancer 2015;121:3853–3861. © 2015 American Cancer Society.